Assessing aerosol changes over Delhi using satellite and ground measurement data: Insights from a COVID-19 lockdown period - Nguyen-Thuy, Huong; Ngo-Duc, Thanh; Dam-Duy, An (Vietnam Journal of Earth Sciences, 2024)
The tragic COVID-19 pandemic, while presenting numerous devastating consequences, has inadvertently provided a unique opportunity for studying air pollution. In this study, we specifically evaluate the spatiotemporal changes in aerosols before and during the COVID-19 lockdown from March to May 2020 over Northwest India, with a particular focus on two subregions in the vicinity of Delhi: Delhi-West and Delhi-East. The assessment was conducted using aerosol optical depth (AOD) data from the Moderate Resolution Imaging Spectroradiometer (MODIS) mission, aerosol profiles from the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) mission, and ground-based measurements of PM2.5 and PM10. Results demonstrated evident reductions in surface particulate matter and AOD during the lockdown. Approximately 40% of the contribution to the total AOD was from aerosols below 1 km. Different rates of change in AOD were observed for the two subregions across different lockdown phases, attributed to differences in emission sources: Delhi-East is more influenced by residential emissions, while Delhi-West is more affected by natural sources. The surface concentration and variabilities of PM2.5 and PM10 confirmed the differences between the two subregions, emphasizing the role of anthropogenic activities in PM2.5 emissions over the study area.